2008
DOI: 10.1126/science.1160606
|View full text |Cite
|
Sign up to set email alerts
|

Flood or Drought: How Do Aerosols Affect Precipitation?

Abstract: Aerosols serve as cloud condensation nuclei (CCN) and thus have a substantial effect on cloud properties and the initiation of precipitation. Large concentrations of human-made aerosols have been reported to both decrease and increase rainfall as a result of their radiative and CCN activities. At one extreme, pristine tropical clouds with low CCN concentrations rain out too quickly to mature into long-lived clouds. On the other hand, heavily polluted clouds evaporate much of their water before precipitation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

78
1,687
5
17

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,887 publications
(1,787 citation statements)
references
References 56 publications
78
1,687
5
17
Order By: Relevance
“…Over land, the decrease of light precipitation may be connected with human activities, ranging from increased anthropogenic aerosols from air pollution to changed land-surface coverage. In the past, many studies attributed the decreased light precipitation to increased aerosols [6,8]. These studies argued that increased aerosols can significantly increase the cloud droplet number concentration and reduce droplet sizes, leading to a significant decline in raindrop concentration.…”
Section: Responses Of Global Precipitation Spectra To Global Warmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Over land, the decrease of light precipitation may be connected with human activities, ranging from increased anthropogenic aerosols from air pollution to changed land-surface coverage. In the past, many studies attributed the decreased light precipitation to increased aerosols [6,8]. These studies argued that increased aerosols can significantly increase the cloud droplet number concentration and reduce droplet sizes, leading to a significant decline in raindrop concentration.…”
Section: Responses Of Global Precipitation Spectra To Global Warmingmentioning
confidence: 99%
“…Heavy precipitation usually forms in fastgrowing convective clouds, which are intimately connected with robust moisture rising caused by dynamic convergence, orographic uplifting or surface heating [2][3][4]. In contrast, low-intensity precipitation is more associated with cloud microphysical processes, which are affected by aerosols, moisture content and so on [5][6][7][8].…”
mentioning
confidence: 99%
“…1 To better understand the impact of atmospheric aerosol particles, a detailed picture of their formation and evolution processes is required.…”
Section: Introductionmentioning
confidence: 99%
“…The invigoration mechanism, which refers to deeper and larger clouds with larger mass that develop under polluted conditions, was studied mainly in deep convective clouds (Andreae et al, 2004;Koren et al, 2005;Rosenfeld et al, 2008;Tao et al, 2012;Fan et al, 2013;Hazra et al, 2013a;Altaratz et al, 2014). Our focus here is on warm-cloud fields for which previous observational studies reported an invigoration effect or a non-monotonic response of the clouds to an increase in aerosol loading.…”
Section: Introductionmentioning
confidence: 99%